THE ANTAGONISM MECHANISM OF ENDOPHYTIC FUNGI FROM MUNG BEAN TO Cercospora canescens - Tunjung Pamekas; Nadrawati; Usman Kris Joko Suharjo; Reksi Dimas Danendro (Jurnal Ilmu-Ilmu Pertanian Indonesia, 2024)
Cercospora leaf spot disease is severely damaging to mung bean plants and causes yield loss of 60% more. Pathogenic infections can give rise to leaf spots, widen rapidly, and cause premature defoliation of the leaves so they are often considered a sign of harvest. Biological control using endophytic fungi derived from mung bean plants themselves is very necessary. The purpose of the study was to evaluate the antagonism mechanism of endophytic fungi to Cercospora canescens. The endophytic fungus was isolated from the mung bean plant tissue and double-cultured with C. canescens. The percentage of inhibition and the mechanism of antagonism of each endophytic fungus was observed. From the results of the study, 15 species of fungi were obtained, namely Aspergillus flavus 1, Fusarium sp. 1, CE5, CE10, Rhizoctonia sp., Aspergillus sp.1, Fusarium sp. 2, Cladophialophora sp., CE6, Aspergillus sp. 2, Phytium sp., CE4, CE13, Aspergillus flavus 2, and Aspergillus sp. 3.The percentage of inhibition of 15 species of endophytic fungi against C. canescens ranged from 5.13 to 50.0% with antagonistic mechanisms in the form of competition for space, nutrients, and oxygen; some species of endophytic fungi have antibiotics and lysis-parasitism. Endophytic fungi are able to compete in the absorption of carbohydrates, proteins, essential amino acids, minerals, and microelements such as phosphates, magnesium, potassium, C vitamins, and B vitamins. Antibiotics through the production of antimicrobial compounds in the form of enzymes, toxins, or antibiotics are produced by endophytic fungi. The coil around of pathogenic hyphae until pathogenic hyphae lysis and die is the last mechanism carried out by endophytic fungi. The role of endophytic fungi as an inducer of plant resistance to pathogens in the field needs to be evaluated.